Does Financial Performance As An Intervening Variable In Strengthening Market Value: Intellectual Capital Approach - Sriyono Sriyono; Detak Prapanca; Ainnur Rosyidah (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: This research aims to determine the effect of intellectual capital on market value with financial performance as an intervening variable. Design/methodology/approach: This study uses quantitative methods, the population used in this study is mining companies listed on the Indonesia Stock Exchange, sampling techniques used are purposive sampling, sampling obtained 55 companies. Findings: This study indicates that there is a relationship between the intellectual capital variable influences Return on Assets. Research limitations/implications: The analysis technique used in this study is path analysis with the Smart PLS 3.0 program's help. Intellectual capital influences market value. Intellectual capital affects the Asset Turn Over. Return on Assets does not affect market value. Asset Turn Over affects market value. This study concludes that Intellectual capital has no effect on market value with return on Asset as an intervening variable.. Practical implications: This study concludes that Intellectual capital has no effect on market value with return on Asset as an intervening variable. Intellectual capital does not affect market value with asset turn over as an intervening variable. Paper type: Research paper